THE EFFECTIVENESS OF TEACHING SPEAKING BY USING THINK PAIR SHARE TECHNIQUE AT FIRST GRADE OF SMPN 1 SEMEN - Ratnawati, Dwi (LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research is aimed to know the effectiveness of teaching speaking by using think pair share technique at the first year students of SMPN 1 Semen. The research is designed in experimental research which is using quesionare, pretest, and posttest as the data collection and the treatment to give the teaching material by the method of teaching, think pair share technique. The result of study showed the significant difference between pre-test and post-test. By SPSS calculation, the pre-test 39.45, post test 58.89, and the result of t-test by using SPSS 17.0 version is 26.24.The sig. 2-tailed shows 0,000. It means that the result is significant in 1% significance level. So it can be conclude that learning speaking by using think pair share technique at the first year students of SMPN 1 Semen is effective. The result of this study recommended for the teacher to give the suitable technique to teach speaking.